2015
DOI: 10.3855/jidc.5416
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of hepatitis B virus infection among Chinese schizophrenia patients

Abstract: Introduction: This study aimed to analyze the characteristics of HBsAg, HBsAb, coexistence of HBsAg and HBsAb, and the genotypic distribution of HBV in Chinese schizophrenia patients. Methodology: A total of 1,694 schizophrenia patients, 9-85 years of age, were recruited for the present study. HBsAg, HBsAb, and HBV DNA were detected with commercial methods. ALT, AST, γ-GT, TBIL, and IBIL were measured by an automatic biochemistry analyzer. All statistical analyses were performed with SPSS 13.0. Results: The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Recently, we reported that the seroprevalence of HBsAg was 11.0% in Chinese adult schizophrenia patients, compared with 7.18% in the general population [12]. Furthermore, although hepatitis B vaccination results in protection of a high proportion (95%) of infants, children, and young adults, the efficacy of hepatitis B vaccine in schizophrenia patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that the seroprevalence of HBsAg was 11.0% in Chinese adult schizophrenia patients, compared with 7.18% in the general population [12]. Furthermore, although hepatitis B vaccination results in protection of a high proportion (95%) of infants, children, and young adults, the efficacy of hepatitis B vaccine in schizophrenia patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia and related psychiatric disorders have been associated with higher detection rates of viral infection, including hepatitis B virus (HBV) ( Klinkenberg et al, 2003 ; Rosenberg et al, 2001 ; Zhu et al, 2015 ; Lluch and Miller, 2019 ), hepatitis C virus (HCV) ( Rosenberg et al, 2001 ; Lluch and Miller, 2019 ), and human immunodeficiency virus (HIV) ( Rosenberg et al, 2001 ), which may be due to increased infection susceptibility and environmental risk factors ( Lluch and Miller, 2019 ). Schizophrenia has also been correlated with altered cytokine levels and inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has increasingly been reported to be related to severe mental illness, [4] such as schizophrenia, which is a chronic psychiatric disorder characterized by cognitive impairment [5] . Several studies have investigated the prevalence of viral hepatitis, especially HBV and HCV, in patients with schizophrenia [6–11] . Hung et al [6] reported that the seroprevalence of HBV and anti-HCV surface antigens was 10.4% and 1.9%, respectively, among 590 patients with schizophrenia in Taiwan, whereas Sockalingam et al [10] found an HCV prevalence (antibody and viremia positivity) of 2.7% in 110 patients with schizophrenia in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Several studies have investigated the prevalence of viral hepatitis, especially HBV and HCV, in patients with schizophrenia. [6][7][8][9][10][11] Hung et al [6] reported that the seroprevalence of HBV and anti-HCV surface antigens was 10.4% and 1.9%, respectively, among 590 patients with schizophrenia in Taiwan, whereas Sockalingam et al [10] found an HCV prevalence (antibody and viremia positivity) of 2.7% in 110 patients with schizophrenia in Canada. Patients with viral hepatitis, including HBV and HCV, have a high risk of liver cancer, especially hepatocellular carcinoma (HCC).…”
Section: Introductionmentioning
confidence: 99%